2023
DOI: 10.3390/nu15143206
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry Leaves and Extracts-Molecular Mechanism of Action and Its Effectiveness on Human Cervical Ripening and the Induction of Labor

Abstract: The gestational period is an incredibly stressful time for a pregnant woman. Pregnant patients constantly seek effective and reliable compounds in order to achieve a healthy labor. Nowadays, increasing numbers of women use herbal preparations and supplements during pregnancy. One of the most popular and most frequently chosen herbs during pregnancy is the raspberry leaf (Rubus idaeus). Raspberry extracts are allegedly associated with a positive effect on childbirth through the induction of uterine contractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…Nevertheless, the anti-inflammatory effect of RiDE is obtained due to the synergistic effects of various polyphenol compounds. That is, its beneficial effect is supported by its well-known utilization in traditional herbal medicine for centuries, having been used to treat many ailments associated with the female reproductive system, particularly during pregnancy, and to aid in childbirth, with long-lasting effects seen into the modern day [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the anti-inflammatory effect of RiDE is obtained due to the synergistic effects of various polyphenol compounds. That is, its beneficial effect is supported by its well-known utilization in traditional herbal medicine for centuries, having been used to treat many ailments associated with the female reproductive system, particularly during pregnancy, and to aid in childbirth, with long-lasting effects seen into the modern day [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that raspberry leaf extract may lead to significant clinical down-regulation and inhibition of intestinal CYP3A4 (an element of the cytochrome P450 superfamily), thereby significantly changing the absorption and pharmacokinetics of the drugs taken, and even inhibiting the cervical ripening process. The ellagic acid contained in raspberry will shorten the clotting time and increase the activity of thrombin, which will lead to more pain in the delivery process ( Socha et al, 2023 ). Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by abnormal glucose clearance and inadequate insulin response.…”
Section: Pharmacological Effects and Applications Of Raspberrymentioning
confidence: 99%